HYPERBOLE IN ALBUM “V” BY MAROON 5 - mau, ardy (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
This article discusses the hyperbole figure used in the song lyrics of Maroon 5’s album entitled “V”. The author thoughts hyperbole is used create strong feelings in the mind of the listener by comparing an emotion to an object, experience, or event, or a songwriter might also use hyperbole to create vivid images in the mind of a listener. The data is taken from Maroon 5’s album entitled “V” released in 2014.This study aims to identify the types and find the meaning of the hyperbola language in the song. To analyze the data, the main theory used in this article is the figurative language theory proposed by Knickerbocker and Reninger (1963), the theory of meaning proposed by Leech (1981) and some of another supporting theory. This article uses qualitative methods to provide a clear picture of the problems identified. Descriptive study in textual analysis is applied to describe the types and meanings of hyperbolic figures in the song lyric. Keywords: Hyperbole, song lyric,Maroon 5